1998
DOI: 10.1016/s0266-7681(98)80071-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Management of Traumatic Posterior Interosseous Nerve Palsy

Abstract: The clinical features and results of treatment were reviewed in 17 traumatic palsies of the posterior interosseous nerve. Variations in clinical features depended on whether the recurrent branch or descending branch of the posterior interosseous nerve was injured. Seven patients had nerve repair, and two were treated by tendon transfers. Eight patients were treated conservatively. Sixteen of 17 patients recovered to more than M4 motor power at final follow-up. Associated muscle damage worsened the functional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 18 publications
0
44
0
8
Order By: Relevance
“…Type III (drop thumb), was due to a compression of the descending branch alone. Conversely traumatic palsies of the PIN have different characteristics compared to non-traumatic palsies of the PIN (Spinner et al, 1988;Hirachi et al, 1998;Leechvavengvongs et al, 2001). The traumatic PIN palsies were classified and categorized into three types by Hirachi et al (1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type III (drop thumb), was due to a compression of the descending branch alone. Conversely traumatic palsies of the PIN have different characteristics compared to non-traumatic palsies of the PIN (Spinner et al, 1988;Hirachi et al, 1998;Leechvavengvongs et al, 2001). The traumatic PIN palsies were classified and categorized into three types by Hirachi et al (1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the traumatic or non-traumatic lesions of terminal motor branches of the PIN end up as isolated drop thumb deformity (Suematsu and Hirayama, 1988;Hirachi et al, 1998;Hirayama and Takemitsu, 1998), isolated drop fingers (Cravens and Kline, 1990;Hirachi et al, 1998) , and the sign of horns (Spinner et al, 1998;Leechvavengvongs et al, 2001). Detailed anatomic knowledge of the terminal motor branches of the PIN is required for a correct diagnosis and surgery and most of the studies did not look into the correlation between the anatomy and the clinical outcome with the exception of a few (Spinner et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Elbow pain is one of the most frequent presenting symptoms but was not noted in this case. Lipomas are the most common cause of PIN palsy, [5][6][7][8][9] the second most commonest being iatrogenic or post-traumatic [2,3,6,8,[10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Various causes for PIN palsy have been described, the commonest being secondary to lipoma with other rare causes of periosteal lipoma [4], inflammatory synovium associated with rheumatoid arthritis, pigmented villonodular synovites (PVNS), post traumatic [7] iatrogenic, direct injuries and following radial head fracture or dislocation in a Monteggia fracture all noted Although the unilateral tardy PIN palsy has been described in a Monteggia fracture before to the best of our knowledge bilateral tardy PIN palsy have never previously been reported in the literature. We present a rare case of bilateral PIN palsy secondary to congenital dislocation of the radial head [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Following the acute injury and anterior dislocation of the radial head, direct trauma and traction neuropraxia are implicated [36]. However, several authors [5,15,35,39] have reported that these acute neuropraxias resolve with observation following closed reduction of the radial head.…”
Section: Discussionmentioning
confidence: 99%